On using ABC for deriving distinguishing sequences for Verilog-descriptions - Kushik N. G. Nataljya Gennadjevna; Evtushenko N. V. Nina Vladimirovna; Torgaev S. N. Stanislav Nikolaevich; Shatilov N. P. Nikita Petrovich (2016, 2016)
Title screen